Nanostructured Powders of AA7075 - SiC Manufactured by High-Energy Ball Milling in a Bath of Isopropyl Alcohol - Wésia Amanda de Oliveira Barbosa; Euclides Apolinário Cabral de Pina; Alexandre Douglas Araújo de Moura; Pilar Rey Rodrigues; Oscar Olímpio de Araújo Filho; Ivanilda Ramos de Melo; Heronilton Mendes de Lira (Materials Research, 2023)
In this study, aluminum alloy 7075 (AA7075) nanopowders were prepared by High-Energy Ball Milling (HEBM) in a bath of isopropyl alcohol. The process was investigated in different milling times and silicon carbides (SiC) reinforcement percentual. The effects of these parameters on the samples were characterized by X-ray diffraction (XRD), Laser Diffraction (LD), Scanning Electron Microscopy (SEM), and Energy Dispersive Spectroscopy (EDS). The XRD analyses showed that as the grinding time increases, the micro deformation also increases, while the crystallite and particle size decrease until a constant value at 480 min. If the percentual of SiC reinforcement increases until 5 percent, there is a minimum change in the results compared to AA 7075 milling 480 min with no reinforcement. On the other hand, when the AA7075 was milled for 480 min and reinforced by 10 percent SiC, the best structural refinement result was achieved.